Peranan Government Supports dalam Memoderasi Pengaruh Orientasi Kewirausahaan dan Digital Marketing terhadap Kinerja Pemasaran (Studi Kasus UMKM Kota Soppeng) - Mannawang, Annisa Ath-Thahirah; Syaharuddin, Syaharuddin (Study of Scientific and Behavioral Management, 2024)
This research aims to determine the role of government support in moderating the influence of entrepreneurial orientation and digital marketing on the marketing performance of MSMEs in the food and beverage industry sector in Soppeng Regency. This research uses primary data and secondary data, the sampling technique in this research is using a non-probability sampling technique using the Hair formula, so the total sample in this research is 110 respondents.This type of research is associative research using a quantitative approach, the data analysis technique in this research is using Structural Equation Modeling (SEM) with the help of SmartPLS version 4.0 for Windows, which is directed at answering the mass formulation or hypothesis that has been formulated in this research and is directed to test the relationship between the Government Support variable, the Entrepreneurial Orientation variable, and the Digital Marketing variable on Marketing Performance which is directed at answering the problem formulation and hypothesis in this research.These results show that Entrepreneurial Orientation has a positive and significant influence on Marketing Performance, Digital Marketing has a positive and significant influence on Marketing Performance, Government Support moderates the influence of Entrepreneurial Orientation on Marketing Performance, Government Support moderates the influence of Digital Marketing on Marketing Performance. Keyword: Government Support, Entrepreneurial Orientation, Digital Marketing, Marketing PerformanceThis research aims to determine the role of government support in moderating the influence of entrepreneurial orientation and digital marketing on the marketing performance of MSMEs in the food and beverage industry sector in Soppeng Regency. This research uses primary data and secondary data, the sampling technique in this research is using a non-probability sampling technique using the Hair formula, so the total sample in this research is 110 respondents.This type of research is associative research using a quantitative approach, the data analysis technique in this research is using Structural Equation Modeling (SEM) with the help of SmartPLS version 4.0 for Windows, which is directed at answering the mass formulation or hypothesis that has been formulated in this research and is directed to test the relationship between the Government Support variable, the Entrepreneurial Orientation variable, and the Digital Marketing variable on Marketing Performance which is directed at answering the problem formulation and hypothesis in this research.These results show that Entrepreneurial Orientation has a positive and significant influence on Marketing Performance, Digital Marketing has a positive and significant influence on Marketing Performance, Government Support moderates the influence of Entrepreneurial Orientation on Marketing Performance, Government Support moderates the influence of Digital Marketing on Marketing Performance. Keyword: Government Support, Entrepreneurial Orientation, Digital Marketing, Marketing Performance